Time series of optical spectra of Nova V659 Sct. Issue 8 (20th July 2020) - Jack, Dennis; Schröder, Klaus‐Peter; Eenens, Philippe; Wolter, Uwe; González‐Pérez, José Nicolás; Schmitt, Jürgen H. M. M.; Hauschildt, Peter H.
Abstract: With our robotic 1.2 m TIGRE telescope, we were able to obtain eight optical spectra with intermediate resolution ( R  ≈ 20, 000) of the Nova V659 Sct during different phases of its outburst. We present a list of the lines found in the Nova spectra. The most common features are H I, O I, Na I, Fe II, and Ca II. Studying the spectral evolution of the strong features, we found that the absorption features move to higher expansion velocities before disappearing, and the emission features show (different) asymmetries. Because of the intermediate spectral resolution, we identified and analyzed the interstellar medium absorption features present in the spectra. We detected atomic absorption features of Na I and Ca II. The sodium D lines show more complex substructures with three main absorption features at a velocity of around −10, 30, and 85 km s −1 . We identified several diffuse interstellar bands (DIBs) in the Nova V659 Sct spectra and determined their velocities and equivalent widths.